Language, Race, and Critical Conversations in a Primary‐Grade Writers' Workshop. (28th June 2019) - Hartman, Paul; Machado, Emily
Abstract: Despite a wealth of scholarship documenting its linguistic complexity, students in the United States are rarely encouraged to speak or write in African American Language (AAL) in their primary classrooms. The authors documented how one teacher and his highly diverse second‐grade class examined, explored, and experimented with AAL in an instructional unit focused on poetry. Using qualitative research methods, the authors look closely at one student‐initiated conversation about language and race in which students began to notice and name elements of AAL. The authors then examine a classroom discussion focused on the contrastive elements of Dominant American English and AAL. Next, the authors showcase how students took up some of AAL's phonological and grammatical features in their own poetry writing. The authors conclude by offering suggestions for teachers who wish to support an exploration of language diversity in their own classrooms.